Implementasi Metode Fuzzy Tsukamoto Untuk Prediksi Produksi Ikan Gurame Usaha Budidaya Penangkaran - Bima Kurniawan; Dede Andira; Ogi Wahyudi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2020)
Carp is one type of fish introduced recently which is in great demand, because it has the advantage of resistance to disease and fast growth (80-100) days. At present many agricultural areas are utilized as ponds as in sleman. Fuzzy Tsukamoto is one method that is able to calculate and predict according to the data criteria used to get the optimal value in a process, especially in the problems of carp farming. Tsukamoto's Fuzzy Method is first performed to determine its membership function, then to determine the rules, and later the categories will be clustered to each group according to the rules applied. The Tsukamoto method used is the Center Average Defuzzifier method. The conclusion obtained from this study is the use of Fuzzy Logic with the Tsukamoto method can determine the prediction results of demand for gouramy stock as much as 64.9 kg.